Perkembangan Hukum Jaminan Fidusia Berkaitan dengan Hak Cipta sebagai Objek Jaminan Fidusia - Rindia Fanny Kusumaningtyas (Pandecta Research Law Journal, 2016)
Completion of the arrangement concerning copyright provides many benefits for the creator as the owner of copyright or copyright holders. This study is aimed to determine the legal arrangements fiduciary whose object is the copyrighted work that would more clearly the basic laws that govern them and what is the basis of a work can be made the object of fiduciary guarantee and proof of collateral in the form of what is and to know clearly the registration procedure fiduciary object of copyright works /creation.The method used in this research is qualitative method with normative juridical approach with greater emphasis on the analysis of a legislation in force. The result of this research reveals that the latest development is currently in the Act Number 28 of 2014 in addition to the offense becomes a crime on complaint, to a copyright work / creation of an object can be used as fiduciary. This means that a creature can as collateral for the repayment of debt due in a work related to economic rights.